Umbilical cord blood stem cells: clinical application of allogeneic material, problems and perspectives of banking - Goltsev, Anatoliy; Kalynychenko, Tetiana (Problems of Cryobiology and Cryomedicine, 2020)
Abstract: Human umbilical cord blood (UCB) is an important source of hematopoietic stem cells (HSCs), successfully used for allogeneic transplantation to treat a wide range of serious diseases. This article discusses a number of topical problems associated with the functioning of public low-temperature banks of UCB. The principles of standardization, quality control and the effective selection of the cryopreserved units at the transplant centers request are considered from the point of view of the world transplantation practice for this unique biological material. The issues related to the trends in therapy using mesenchymal stromal/stem cells from the fetoplacental complex tissues and their cryopreservation are also deliberated. Special attention is paid to the issues of biomedical ethics and the prospects of public UCB bank establishing in Ukraine, its role in the development of the national HSCs unrelated transplantation. Probl Cryobiol Cryomed 2020; 30(3): 213–235